2006
DOI: 10.1128/jcm.44.3.909-915.2006
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genotyping of SHV β-Lactamase Variants by Mass Spectrometry after Base-Specific Cleavage of In Vitro-Generated RNA Transcripts

Abstract: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) after base-specific cleavage of PCR-amplified and in vitro-transcribed bla SHV genes was used for the identification and genotyping of SHV ␤-lactamases. For evaluation, bla SHV stretches of 21 clinical Enterobacteriaceae isolates were PCR amplified using T7 promoter-tagged forward and reverse primers, respectively. In vitro transcripts were generated with T7 RNA and DNA polymerase in the presence of modified analogues r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
3
2
0
4
Order By: Relevance
“…We were thus able to associate the mass peaks at 2009.51 m/z and 4434.70 m/z present in the proteomes of the isolates, which were grown in the presence of trimethoprim-sulfamethoxazole, as β-lactamases of the SHV type. This data corroborates the genotype obtained in isolates with resistance to this antibiotic and with the masses obtained in the study by Sturenburg et al [34]. In this sense, the detection of modifications in this family may become crucial in preventing newly emerged resistances from spreading.…”
Section: Ampicilinsupporting
confidence: 91%
See 2 more Smart Citations
“…We were thus able to associate the mass peaks at 2009.51 m/z and 4434.70 m/z present in the proteomes of the isolates, which were grown in the presence of trimethoprim-sulfamethoxazole, as β-lactamases of the SHV type. This data corroborates the genotype obtained in isolates with resistance to this antibiotic and with the masses obtained in the study by Sturenburg et al [34]. In this sense, the detection of modifications in this family may become crucial in preventing newly emerged resistances from spreading.…”
Section: Ampicilinsupporting
confidence: 91%
“…Nevertheless, results with cross-validation of model generation were 88.43%, 79.41%, and 75.17% for Genetic Algorithm, Supervised Neural Network, and Quick Classifier, respectively, showing that the peaks were indeed accurately detected even if only by one algorithm. Peaks reported by Sturenburg et al for the strains exposed to tetracycline were not observed here [34]. These tetracycline-producing streptomyces present important signal and protein spectra in the mass range of 2 to 20 kDa.…”
Section: Tetracyclinementioning
confidence: 43%
See 1 more Smart Citation
“…In another investigation, Stürenburg et al implemented the MALDI-TOF MS to analyze fragment masses of base-specific cleavage of bla SHV PCR products after in vitrogenerated RNA transcription. Twenty-one Ent possessing different SHV-types were identified unambiguously and in perfect accordance to the PCR/sequencing results (Sturenburg, et al, 2006).…”
Section: Maldi-tof Mssupporting
confidence: 71%
“…implemented the MALDI-TOF MS to analyze fragment masses of base-specific cleavage of bla SHV PCR products after in vitro -generated RNA transcription. Twenty-one Ent possessing different SHV-types were identified unambiguously and in perfect accordance to the PCR/sequencing results (Sturenburg, et al, 2006). …”
Section: Mass Spectrometry-based Methodologiessupporting
confidence: 60%